2021
DOI: 10.48550/arxiv.2110.06171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicommodity routing optimization for engineering networks

Alessandro Lonardi,
Mario Putti,
Caterina De Bacco

Abstract: Optimizing passengers routes is crucial to design efficient transportation networks. Recent results show that optimal transport provides an efficient alternative to standard optimization methods. However, it is not yet clear if this formalism has empirical validity on engineering networks. We address this issue by considering different response functions-quantities determining the interaction between passengers-in the dynamics implementing the optimal transport formulation. Particularly, we compare a theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We briefly describe the model of [23] to find optimal paths in multilayer networks using optimal transport theory. It considers two main quantities on network edges: fluxes F e of passengers traveling through edge e and conductivities µ e determining F e passing through an edge e. To keep track of the various routes that passengers have, they consider a multi-commodity approach [22,24], by distinguishing passengers based on their entry station i ∈ S. With this approach, the flux F e is an Mdimensional vector, where entries F i e denote the flux of passengers of type i traveling on edge e. We assume the fluxes are determined by pressure potentials p i u and p i v defined on nodes as follow:…”
Section: Optimal Transport For Traffic Distribution In Multilayer Net...mentioning
confidence: 99%
“…We briefly describe the model of [23] to find optimal paths in multilayer networks using optimal transport theory. It considers two main quantities on network edges: fluxes F e of passengers traveling through edge e and conductivities µ e determining F e passing through an edge e. To keep track of the various routes that passengers have, they consider a multi-commodity approach [22,24], by distinguishing passengers based on their entry station i ∈ S. With this approach, the flux F e is an Mdimensional vector, where entries F i e denote the flux of passengers of type i traveling on edge e. We assume the fluxes are determined by pressure potentials p i u and p i v defined on nodes as follow:…”
Section: Optimal Transport For Traffic Distribution In Multilayer Net...mentioning
confidence: 99%
“…This result is complementary to the hierarchical formation of trees since loops provide alternative routes to accommodate fluctuations or guarantee robustness against broken links. Recently, loops formation has also been observed in multicommodity setups [27,28], where the loads are deterministic inputs of the problem. In this case, loops generation is a consequence of having different types of mass-commodities-interacting in a unique shared infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, optimal transport of mass in networks is set as a minimization problem where resources moving through the edges have to satisfy a set of constraints, e.g., conservation of mass, while minimizing a suitable transportation cost [1,3,19,[23][24][25][26][27][28][29][30]. Several efficient methods have been proposed to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal Transport (OT) is a powerful method for computing the distance between two data distributions. This problem has a cross-disciplinary domain of applications, ranging from logistic and route optimization [1][2][3], to biology [4,5] and computer vision [6][7][8][9], among others. Within this broad variety of problems, OT is largely utilized in machine learning [10], and deployed for solving classification tasks, where the goal is to optimally match discrete distributions that are typically learned from data.…”
mentioning
confidence: 99%
“…Notice that for M = 1 and Γ = 1, we recover the standard unicommodity OT setup. Our choice of using the 2-norm over a in J Γ is motivated by recent works [2,28,29] where it is shown that Eq. ( 1) corresponds to Joule's law, while transport paths follow Kirchhoff's law enforcing conservation of mass.…”
mentioning
confidence: 99%